PBMC and exosome-derived Hotair is a critical regulator and potent marker for rheumatoid arthritis - Song, Jinsoo; Kim, Dongkyun; Han, Jiyeon; Kim, Yunha; Lee, Myeungsu; Jin, Eun-Jung (Clinical and experimental medicine, 2015)
Despite growing importance of long non-coding RNAs (lncRNAs) in normal physiological and disease conditions, our knowledge of RA-related lncRNAs remains limited. Therefore, we aimed to identify lncRNA signatures that have prognostic values in RA. There was a notably high expression level of Hotair in blood mononuclear cells and serum exosome of rheumatoid arthritis (RA) patients, leading the migration of active macrophage. In contrast, markedly lower level of Hotair was detected in differentiated osteoclasts and rheumatoid synoviocytes and enforced expression of Hotair led to significantly decreased levels of MMP-2 and MMP-13. This exploratory study provides novel empirical evidence that Hotair could be one of potential biomarkers for diagnosing RA.